Multiple Substance Use Disorders and Self-Reported Cognitive Function in U.S. Adults: Associations and Sex-Differences in a Nationally Representative Sample - Bourgault, Zoe; Rubin-Kahana, Dafna Sara; Hassan, Ahmed Nabeel; Sanches, Marcos; Le Foll, Bernard (Frontiers in Psychiatry, 2022)
Polysubstance use is a growing public health concern that has been associated with poor clinical outcomes. Compared to single-drug users, this population suffers greater deficits in cognitive function, which hinder treatment success and recovery. Despite its high prevalence and poor prognosis, epidemiological research on polysubstance use and accompanying cognitive profile is lacking. We investigated associations between numbers of past-year co-occurring substance use disorders (SUDs) and self-reported cognitive function using data from the National Epidemiologic Survey for Alcohol and Related Conditions III (NESARC-III). Regression analyses revealed a significant negative association between cognitive scores and numbers of past-year SUDs, which was moderated by sex. After adjusting for confounding variables, greater numbers of SUDs were associated with declining self-reported cognitive function, and this relationship was stronger among females. Our findings expand on current literature on cognitive impairments among polysubstance users and provide a novel, nuanced description of this relationship among the general population. We highlight the need for targeted and individualized treatment approaches in order to improve outcomes in this population.